2016
DOI: 10.1002/pen.24456
|View full text |Cite
|
Sign up to set email alerts
|

Dually reinforced all-polyamide laminate composites via microencapsulation strategy

Abstract: A new two‐stage strategy is disclosed for the preparation of all‐polyamide laminate composites based on polyamide 6 (PA6) matrices reinforced by high volume fractions of polyamide 66 (PA66) textile structures and three different types of nanoclays. In the first stage, PA6 microcapsules (MC) loaded with montmorillonite nanoclays (MMT) are synthesized by activated anionic ring‐opening polymerization of ε‐caprolactam in solution in the presence of three different organically treated MMT brands. In the second stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…In the recent paper Dencheva et al [197] produced PA-6-based SPCs with dual reinforcements. The reinforcement contained organophilic montmorillonite clays (OMMT) and PA-6 fabric layers.…”
Section: Compositesmentioning
confidence: 99%
“…In the recent paper Dencheva et al [197] produced PA-6-based SPCs with dual reinforcements. The reinforcement contained organophilic montmorillonite clays (OMMT) and PA-6 fabric layers.…”
Section: Compositesmentioning
confidence: 99%
“…The in-situ polymerization approach of the low-viscosity monomer ε-caprolactam in the presence of the reinforcing fibers was realized by several research groups. [30][31][32][33][34] The anionic polymerization of ε-caprolactam in the presence of an initiator and activator is well understood. 32,34 The great advantage of this method lies in the lowviscosity of the monomer, which ensures a good wetting of the reinforcing fibers by the in-situ formed matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The in-situ polymerization of ε-caprolactam is often combined with resin transfer molding, reactive injection pultrusion, reactive vacuum infusion or reactive rotational molding methods to prepare PA-composites. 31 The in-situ polymerization can also be used for the preparation of microparticles, which may be suitable for the manufacturing of all-PA composites by powder impregnation. The molding temperature influences the structure and properties of the composite, whereby a higher temperature decreases the caprolactam conversion, but leads to an improved fibermatrix adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Among these hybrid particulate systems, the metal-loaded PA6 MP can be especially interesting for the development of novel lightweight materials with tailored magnetic susceptibility, electric and thermal conductivity, or electromagnetic interference (EMI) shielding properties [9,10]. Recent reports on a PA6-based metal-containing hybrid MP showed that they can be used directly as supports for enzymes in biosensors and biocatalysts [11,12], or be transformed by melt processing into PA6-based composites with particulate or textile reinforcement [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…The first comprehensive structural studies by ssNMR on neat PA6 were reported in the 1980s and 1990s using carbon-13 ( 13 C) [15][16][17][18] or nitrogen-15 ( 15 N) [19][20][21] nuclei. Some of us have also used 13 C-ssNMR, along with other analytical methods, to relate the crystalline structure to the mechanical properties in neat PA6 [22] and PA12 [23]. There exist numerous ssNMR studies on the structure of PA6-based composites, mostly comprising nanosized clays [24].…”
Section: Introductionmentioning
confidence: 99%